2020
DOI: 10.1101/2020.06.16.155853
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Augmenting Signaling Pathway Reconstructions

Abstract: Signaling pathways drive cellular response, and understanding such pathways is fundamental to molecular systems biology. A mounting volume of experimental protein interaction data has motivated the development of algorithms to computationally reconstruct signaling pathways. However, existing methods suffer from low recall in recovering protein interactions in ground truth pathways, limiting our confidence in any new predictions for experimental validation. We present the Pathway Reconstruction AUGmenter (PRAUG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 38 publications
0
8
0
Order By: Relevance
“…Reconstruction algorithms are also adapted to overcome this inherent bias toward the nodes and edges in interactomes. For example, heat diffusion and random walk, together with the edge flux calculation, use node degrees for normalization, while PCSF penalizes highly connected proteins ( Creixell et al, 2015 ; Tuncbag et al, 2016a ; Rubel and Ritz, 2020 ). In this way, false-positive edges belonging to hub nodes are excluded from the final subnetwork.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Reconstruction algorithms are also adapted to overcome this inherent bias toward the nodes and edges in interactomes. For example, heat diffusion and random walk, together with the edge flux calculation, use node degrees for normalization, while PCSF penalizes highly connected proteins ( Creixell et al, 2015 ; Tuncbag et al, 2016a ; Rubel and Ritz, 2020 ). In this way, false-positive edges belonging to hub nodes are excluded from the final subnetwork.…”
Section: Resultsmentioning
confidence: 99%
“…In a recent study, the performance of flux algorithms was shown to exceed the performance of PCSF with default parameters ( Rubel and Ritz, 2020 ). However, the selected set of parameters significantly affects the performance of reconstruction algorithms, especially in PCSF.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Signaling pathways such as Interleukin-9 have been used to assess pathway reconstruction algorithms (e.g. [45,46]) and the group has also used graph-based methods to identify candidate regulators of a non-muscle myosin in Drosophila involved in cellular constriction (e.g. [47]).…”
Section: Graphsmentioning
confidence: 99%